PERSEPSI MAHASISWA TENTANG KETIDAK-JUJURAN AKADEMIK: STUDI KASUS MAHASISWA PROGRAM VOKASI UNIVERSITAS INDONESIA - Heri Yuliyanto (Jurnal Vokasi Indonesia, 2015)
AbstractOften we see students gathered tasks given by the lecturers and they are copying answers betweenstudents and others. They perform this action with no load, even though the task is an individualtask. Do they know that what they are doing is an action that is contrary to the basic values ofacademic integrity. Or perhaps they are not aware that they are not a violation, since they merelyimitate or follow the habits of seniors or friends the same age. Then comes the question "How dothey (students) do dishonesty (cheating)?" And "Why are or what background they commit acts ofacademic dishonesty?"Based on the analysis of primary data obtained by distributing a questionnaire to students vocationalprogram UI, and secondary data obtained from the data of students who cheat (academic violations),namely cheating Even during the period 2012/2013 to 2014/2015 Odd and continued to look atstudent biographical data and results academic evaluation found that women students areproportionally larger than the act of cheating men , furthermore student selection process throughSIMAK UI has a proportionally larger than the students that the selection process through PPKB.Keywords:. SIMAK-UI, PPKB, academic violation, cheating